Social Support, Spiritual Well-Being, and Quality of Life Among MSM and Transgender Women Living with HIV in Rural Thailand - Anongluk Vongtree; Natawan Khumsaen; Wimonpan Sungsakul; Supannee Peawnalaw; Panarat Chenchob; Tassamon Namwong (National Journal of Community Medicine)
Background: HIV/AIDS continues to be a significant public health challenge in Thailand, affecting not only the physical health but also the overall quality of life (QOL) of those living with the virus. Understanding the factors influencing QOL is crucial for developing effective interventions and support systems. This study examined the QOL among men who have sex with men (MSM) and transgender women (TGW) living with HIV in Thailand and identify factors that are associated with their QOL.